2018
DOI: 10.3390/ma11122551
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Dielectric Behaviour of M-Type Hexaferrite/Polymer Nanocomposites

Abstract: In the present study two sets of nanocomposites consisting of an epoxy resin and BaFe12O19 or SrFe12O19 nanoparticles were successfully developed and characterized morphologically and structurally via scanning electron microscopy and X-ray diffraction spectra. The dielectric response of the nanocomposites was investigated by means of broadband dielectric spectroscopy and their magnetic properties were derived from magnetization tests. Experimental data imply that the incorporation of the ceramic nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The coercivity ( H c ) of the magnetic composite filaments did not significantly change and remained nearly constant for all the samples. This indicated that the coercive behavior was controlled by the type of magnetic nanoparticles, but not controlled by the content of magnetic nanoparticles 3 …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The coercivity ( H c ) of the magnetic composite filaments did not significantly change and remained nearly constant for all the samples. This indicated that the coercive behavior was controlled by the type of magnetic nanoparticles, but not controlled by the content of magnetic nanoparticles 3 …”
Section: Resultsmentioning
confidence: 95%
“…In recent years, magnetic composite materials have gained significant attention as a new generation of multifunctional materials 1 that are especially attractive to manufacturers of small motors and actuators for household and automotive use as well as to the audio, video, and computer industries 2 . Magnetic polymeric materials are perhaps the most frequently encountered and widely employed variety of magnetic composite materials, including epoxy resin/M‐type hexaferrite nanocomposites, 3 magnetic cellulose paper/barium hexaferrite, 4 PLA/LNR/NiZn ferrite nanocomposite, 5 Polyaniline/barium ferrite composite, 6 PLA/Fe 3 O 4 melt‐blown nonwoven, 7 and PVDF/barium ferrite composite film, 8 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…M-type hexaferrites are metal oxides with a formula of MFe 12 O 19 . They are frequently utilized as permanent magnets [6]. Apart from the high saturation magnetizations and magneto-crystalline anisotropies, also high intrinsic coercivites; they possess a number of electrical properties as well such as high electrical resistivity, low dielectric loss, low eddy current loss etc [7 -9].…”
Section: Introduction mentioning
confidence: 99%
“…Polymer nanocomposites incorporating inorganic nanomaterials with advanced physicochemical properties receive extensive attention due to their unique advantages, which include ease processing and forming, thermomechanical stability, high dielectric breakdown strength and low cost [12,13,14]. Their electromagnetic properties can be altered by embedding suitable reinforcing inclusions and their dielectric and magnetic response can be tuned by controlling the type and the amount of filler content [15,16,17,18,19,20,21]. These unique properties make polymer nanocomposites, especially those filled with magnetic inclusions, suitable for advanced applications in various fields such as chemical sensors, magnetic recording materials, molecular electronic, electric catalysis, electro-magnetic interference (EMI) shielding, rechargeable battery, microwave absorption materials and corrosion protection coatings [2,3,4,5,6,22,23,24].…”
Section: Introductionmentioning
confidence: 99%